2020
DOI: 10.4271/epr2020008
|View full text |Cite
|
Sign up to set email alerts
|

Unsettled Topics in Unmanned Aerial Vehicle Icing

Abstract: About the Publisher SAE International ® is a global association of more than 128,000 engineers and related technical experts in the aerospace, automotive, and commercial-vehicle industries. Our core competencies are lifelong learning and voluntary consensus standards development. Visit sae.org SAE EDGE™ Research Report Disclaimer SAE EDGE™ Research Reports focus on topics that are dynamic, in which knowledge is incomplete, and which have yet to be standardized. They represent the collective wisdom of a group o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 57 publications
(113 reference statements)
0
15
0
Order By: Relevance
“…For unmanned aerial vehicles (UAVs), icing research has a much shorter history and can be considered an emerging research field. Although the first analysis and reports of at mospheric icing on UAVs date back to the 1990s [2], the research in this area has only recently gained momentum [3]. The reason UAV icing is becoming a trending topic is partly linked to the rise of commercial applications of UAV technologies [4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…For unmanned aerial vehicles (UAVs), icing research has a much shorter history and can be considered an emerging research field. Although the first analysis and reports of at mospheric icing on UAVs date back to the 1990s [2], the research in this area has only recently gained momentum [3]. The reason UAV icing is becoming a trending topic is partly linked to the rise of commercial applications of UAV technologies [4].…”
Section: Introductionmentioning
confidence: 99%
“…Many UAV missions require operations of unmanned aircraft in adverse weather conditions [6]. One of the main barriers to achieving an all-weather capability of UAVs is to mitigate the risk of atmospheric in-flight icing [3].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on UAVs have shown that the Reynolds number has a significant influence on the physics of ice accretion and also on the subsequent aerodynamic performance penalties [16][17][18]. Icing on UAVs is similar to icing on manned aircraft with some key differences related to airframe size, mission profiles, and icing sensitivity [19]. Most UAVs (except for the largest) operate at Reynolds numbers in between large and small wind turbines, typically in the order of Re = 10 5 -10 6 .…”
Section: Introductionmentioning
confidence: 99%